INFLUENCE OF COPPER SOIL CONTAMINATION ON GROWTH AND QUALITY OF ACOITA-CAVALO (Luehea divaricata) AND RED-AROEIRA (Schinus therebinthifolius Raddi.) SEEDLINGS - Silva, Rodrigo Ferreira da (2011)
Copper contamination has become common in areas of mining and grape culture in Rio Grande do Sul. The aim of this study was to evaluate the influence of the dose of copper on growth and seedling  quality of acoita-cavalo and aroeira-vermelha. The experimental design was completely randomized in a factorial scheme (2 x 5), using two forestry species and five copper doses: 0, 64, 128, 192 and 256 mg kg-1 of soil, with five replications. Plant height, collar diameter, dry mass weight of root system and shoot, length and surface specific area of root system and index of seedlings quality were evaluated and relation between shoot height and haste diameter, shoot height  and  shoot dry mass weight and Dickson quality index were assessed. The results showed that the copper doses tested did not change the quality of aroeira-vermelha seedlings but acoita-cavalo displayed better quality with the application of 64 mg kg-1 Cu. Copper primarily affected the acoita cavalo and aroeira-vermelha root system. Aroeira vermelha was more tolerant to copper toxicity than acoita-cavalo and displayed better quality at higher copper doses.